The Globalization of the Agricultural and Food Sector and Theories of the State - Bonanno, Alessandro (The International Journal of Sociology of Agriculture and Food, 1991)
The paper investigates the theoretical dislocation between the domestic oriented character of theories of the State and the transnational character of theories of socio-economic development. Employing the case of the food and agricultural sector, it is argued that the literature in this area has emphasized the transnational dimension of capital accumulation and the process of by-passing State authority at the national level. This situaion mandates a re-evaluation of State theories in regard to the international dimension of current processes of capital accumulation. Furthermore, the present analysis suggests patterns of "contradictory convergence" in which expansion at the transnational level of State action is demanded by transnational corporations and subordinate classes alike. This demand, however, is contradictory, as it finds its limits in the transnational bourgeoisie's desire to avoid State action. Politically, as a result of this situation the locus of emancipatory social action should be increasingly transferred to the international arena.                                                                                                   La globalización del sector agrícola y alimentario y las teorías del estado                                                                           ?Resumen      Este artículo indaga en el desfase teórico existente entre las teorías del Estado, con un carácter orientado hacia lo nacional, y el carácter transnacional de las teorías del desarrollo socio-económico. Con base en el caso del sector agrícola y alimentario, se afirma que la literatura en esta área ha enfátizado la dimensión transnacional de la acumulación de capital y la evasión de la autoridad del Estado en el ámbito nacional. Esta situación requiere revaluar las teorías del Estado en atención a la dimensión internacional del presente proceso de acumilación de capital. Más aún, este análisis sugiere patrones de "convergencia contradictoria" en la cual, la expansión de la acción del Estado a nivel transnacional es exigido tanto por las corporaciones transnacionales como por las clases subordinadas. Esta exigencia, sin embargo, es contradictoria ya que se encuentra limitada por el interés de la burguesía transnacional de evadir la acción del Estado. Desde el punto de vista político, como resultado de esta situación, el espacio de la acción social emancipadora debe trasladarse, cada vez más, a la escena internacional.